Results of Tip Urethroplasty in Distal Penile Hypospadias in Pediatric Patients - Saqib Ismail, Tahseen Ismail, Syed Zakir Hussain Shah, Sadia Rasheed, Aqdas Saqib, Rabia Memon (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Distal penile hypospadias is one of the common congenital abnormality. It is the anomaly of anterior urethral and penile development. Objective: The purpose of the study is to find the outcomes of TIP urethroplasty in distal penile hypospadias in the pediatric patients. Study design: This retrospective study was conducted at the urology department of our institute hospital for the duration of six months from February 2022 to July 2022. Material and Methods: Out of all the patients that visited hospital during a course of 1 year, 250 had distal penile hypospadias. There were 45 individuals that were less than 2 years of age, while the remaining patients were more than 2 years of age. There were 210 patients that were included in the de novo hypospadias type and 40 had recurrent type of hypospadias. Results: Chordee was found in case of 50 patients, most of the patients had their chordee disappeared during the degloving of the penis. Running sutures were in use of 200 patients while 50 reported about interrupted use of suturing. There were 25 patients that used no stent after surgery, however, the stent was used by 150 patients for 3 days. Conclusion: TIP urethroplasty is an effective and reliable method that can be used for the treatment of distal penile hypospadias as it has less rate of complications and is suitable for primary as well as redo operations. It covers neourethra by the moving corpus spongiosum or by any flap. Keywords: TIP urethroplasty and penile hypospadias.